Estimating building materials for home construction - Scherer, Chris; Clews, Vince; Cambridge Educational (Firm). (Monmouth Junction, NJ : Cambridge Educational, 2002)
Exhibits how to estimate the amount of building materials needed for home construction using graphics, formulas, and live-action demonstration.
This program contains an instructor's guide available as a free printable PDF from the website. Download the instructor's guide at www.films.com.
Editor, Jamie Watson.
Keywords: House construction -- Estimates; House construction -- Materials; Quantity surveying